Sistem Informasi Terintegrasi Pada Proses Pendaftaran Dan Menabung Di Bank Sampah Induk Cimahi Berbasis Mobile - Andri Taufiq; Gunawan Abdillah; Faiza Renaldi (Maranatha University Press, 2016)
Bank Sampah Cimahi (Bank Samici) was established with the aim to reduce landfill waste in the city cimahi. So that the waste can be harnessed into something that has economic value. In 2014 to 2016 it was noted that bank customers Bank Sampah Induk Cimahi 825 people, while the population of cimahi in 2014 amounted to 579 015 inhabitants, the comparison between the customer and the number of city dwellers cimahi only 0:23% is already a customer of the population cimahi, certainly in this case waste bank holding cimahi less successful, By utilizing advances in information and communication technology, As we have seen in the current era we already feel very rapid development of technology and growing fast. Among one of the growing communications technology is Mobile Communications Technology. With the development of this mobile technology, to access information and communicate more easily and more quickly. thus requiring mobile-based integrated information system that can attract cimahi citizens to become customers of banks holding junk cimahi that can facilitate in terms of enrollment and saving.